Pemberdayaan Masyarakat di Sekitar Pasar Pertapaan Indrokilo Desa Kemiri Kecamatan Mojosongo - Muhammad, Zakariya; Triatmo, Agus Wahyu (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
The project investigates the empowerment process of the community through the development of a tourism market, including the forms and outcomes of such empowerment. This research employs a qualitative approach with research subjects consisting of village heads, tourism village managers, traders, as well as tourists or visitors to Kemiri Village at the Indrokilo Hermitage Market. Data analysis is conducted through observation, interviews, and documentation. The data analysis process consists of data collection, data reduction, data presentation, and drawing conclusions. As a result, community empowerment activities were initiated on March 27, 2022, and have been ongoing since then. The outcomes of the empowerment demonstrate that the tourism village in Kemiri Village has succeeded and has positive impacts felt by almost the entire village community. With the implementation of various methods and good management practices, the Indrokilo Hermitage Tourism Market can become a tourist destination, an economic supplier for residents, and ultimately contribute to the creative economy. In February, we attempted to calculate the income or improvement in the economy, and it was concluded that this empowerment initiative has been successful, in other words, it has been able to help the economy of the community in Kemiri Village, Mojosonggo, Boyolali.